2006
DOI: 10.1038/sj.ki.5000312
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic risk factors for cardiovascular events in an incident dialysis cohort

Abstract: Cardiovascular disease (CVD) remains the major cause of death in patients with end-stage renal disease (ESRD). Traditional risk factors do not explain the high prevalence of CVD in this population, and other non-traditional cardiovascular (CV) risk markers have now been described. Therefore, the potential relationship between CVD and phenotypic and genotypic risk markers was investigated prospectively in incident dialysis patients cohort. The 279 patients (244 on hemodialysis, 35 on peritoneal dialysis) within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 37 publications
1
29
0
Order By: Relevance
“…A recent analysis of the European Renal Association-European Dialysis and Transplant Association Registry revealed that, despite the increased risk of death associated with HD, no excess of CV mortality is observed [26]. The incidence found in our study is very similar to those reported by the majority of previous studies in European populations, but lower than those observed in US populations [21,23,27]. Additionally, in our study the all-cause and CV mortality rates during the first year were constant, which differs with results from the DOPPS (higher mortality rate during the first 120 days) [27].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…A recent analysis of the European Renal Association-European Dialysis and Transplant Association Registry revealed that, despite the increased risk of death associated with HD, no excess of CV mortality is observed [26]. The incidence found in our study is very similar to those reported by the majority of previous studies in European populations, but lower than those observed in US populations [21,23,27]. Additionally, in our study the all-cause and CV mortality rates during the first year were constant, which differs with results from the DOPPS (higher mortality rate during the first 120 days) [27].…”
Section: Discussionsupporting
confidence: 59%
“…The Dialysis Outcomes and Practice Patterns study (DOPPS) [18,19] demonstrated that the characteristics of incident populations and HD techniques differ from one country to another. Published studies include large populations from the US [20,21], and small cohorts from Japan [22] and Europe [23]. The primary objective of the ANSWER study was to determine patients’ characteristics at HD initiation independently associated with CV morbidity and mortality, in order to find modifiable risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…There is a high prevalence of CVD in patients with ESRD that cannot be explained by traditional risk factors alone. Several reports suggest a role of candidate genes in the pathogenesis of CVD in dialyzed patients [22]. Polymorphisms of genes that are involved in innate immunity might be particularly relevant in increased risk of CVD [23].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports suggest a role of candidate genes in the pathogenesis of CVD in dialyzed patients [21]. Both renal failure and CVD are polygenic disorders with changes in multiple genes involved in their etiopathology.…”
Section: Discussionmentioning
confidence: 99%